Two novel energy crops: Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L. - State of knowledge - Cumplido-Marin, Laura; Graves, Anil; Burgess, Paul J.; Morhart, Christopher; Paris, Pierluigi; Jablonowski, Nicolai D.; Facciotto, Gianni; Bury, Marek; Martens, Reent (MDPI, 2020)
Current global temperature increases resulting from human activity threaten many ecosystems and societies, and have led to international and national policy commitments that aim to reduce greenhouse gas emissions. Bioenergy crops provide one means of reducing greenhouse gas emissions from energy production and two novel crops that could be used for this purpose are Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L. This research examined the existing scientific literature available on both crops through a systematic review. The data were collated according to the agronomy, uses, and environmental benefits of each crop. Possible challenges were associated with high initial planting costs, low yields in low rainfall areas, and for Sida hermaphrodita, vulnerability to Sclerotinia sclerotiorum. However, under appropriate environmental conditions, both crops were found to provide large yields over sustained periods of time with relatively low levels of management and could be used to produce large energy surpluses, either through direct combustion or biogas production. Other potential uses included fodder, fibre, and pharmaceutical uses. Environmental benefits included the potential for phytoremediation, and improvements to soil health, biodiversity, and pollination. The review also demonstrated that environmental benefits, such as pollination, soil health, and water quality benefits could be obtained from the use of Sida hermaphrodita and Silphium perfoliatum relative to existing bioenergy crops such as maize, whilst at the same time reducing the greenhouse gas emissions associated with energy production. Future research should examine the long-term implications of using Sida hermaphrodita and Silphium perfoliatum as well as improve knowledge on how to integrate them successfully within existing farming systems and supply chains.
Keywords: Cup plant; Virginia fanpetals; Virginia mallow; bioenergy crops